Four Central Nanocavity of Ultra-Sensitive Refractive Index Biosensor for Cancer Detection in Hexagonal Photonic Crystal - William Matsui; Jianqiao Fang (Advances in Engineering and Intelligence Systems)
We design and analysis of a novel biosensor with four center nanocavity in hexagonal photonic crystal (PhC) is presented. This biosensor can detect cancer cells from normal cells. The main performance of the detection is based on glass nanocavity and the samples refractive index. In proposed biosensor, four central nanocavities are immersed in the samples and the resonant wavelengths change according to the refractive index. The resonant wavelengths range for the detection of cancer cells is λ0=1.491258µm ~ 1.50588µm. The power loss in the proposed structure is less than 2%, and the delay time is 2ps. At best, the sensitivity and quality factor parameters are 734nm/RIU and Q.f=2330.09, respectively. The Figure of Merit (FOM) or detection limit is 412.87±45.87RIU-1. The biosensor footprint and the design method are 102.6μm2 and FDTD, respectively. Proposed device is a higher speed and sensitivity in detection samples than similar structures.